2016
DOI: 10.1590/0103-8478cr20150531
|View full text |Cite
|
Sign up to set email alerts
|

Extraction yield, antioxidant activity andphenolics from grape, mango and peanut agro-industrial by-products

Abstract: The objective of this study was to determine and correlate the extraction yields, antioxidant activity, total phenolics and total flavonoids from grape, mango and peanut agro-industrial by-products. The β-carotene/linoleic acid autoxidation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The extraction methods show similar yields for each plant part. Several studies reported that the extraction yields are not directly linked with biological activity as well as chemical composition (Anokwuru et al., 2018; Braga et al, 2016; Do et al., 2014). Furthermore, plants have complex matrices containing different compounds decorated with diverse chemical groups that could be extracted by the solvents used.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction methods show similar yields for each plant part. Several studies reported that the extraction yields are not directly linked with biological activity as well as chemical composition (Anokwuru et al., 2018; Braga et al, 2016; Do et al., 2014). Furthermore, plants have complex matrices containing different compounds decorated with diverse chemical groups that could be extracted by the solvents used.…”
Section: Resultsmentioning
confidence: 99%
“…The results of different experimental runs for both HAE and UAE processes are given in the Appendix. The relationship between extraction yield, polyphenol content, and antioxidant activity may reveal the true biological value of plant extracts (Braga et al, ); therefore, these parameters were considered as response variables in this study. The TEY (or EY), TPC (or TPY), and IC 50 in the extracts from HAE process (Step 1) were ranged from 8.74% to 17.52% (or 1.1% to 2.43%), 73.29 to 149.24 mg GAE/g of extract DW (or 19.2 to 38.08 mg GAE/g of leaves DW), and 940.25 to 5,161.79 μg/ml, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results of different experimental runs for both HAE and UAE processes are given in the Appendix. The relationship between extraction yield, polyphenol content and antioxidant activity may reveal the true biological value of plant extracts (Braga et al, 2016); therefore, these parameters were considered as response variables in this study. The TEY (or EY), TPC (or TPY), and IC 50 in the extracts from HAE process (Step 1) were ranged from 8.74% to 17.52% (or Water swells the plant material, allowing ethanol to penetrate the solid matrices more easily to disrupt the bonding between the bioactive compounds and plant matrix, and facilitate a better mass transfer of the compounds (Cujic et al, 2016;Ghitescu et al, 2015).…”
Section: The Comparison and Relationship Between Indicesmentioning
confidence: 99%
“…This variation of the result was due to the climatic condition of the states and the soil nature of the states. Many literatures revealed that plant biomass depends on the soil nature, soil fertility as well as climatic condition and nature of solvent used for the extraction (Anwar et al, 2013;Braga et al, 2016, Das et al, 2016. Thereafter, yield of the extract directly proportional with the plant biomass (Das and Tribedi, 2015).…”
Section: Yield Of the Extractmentioning
confidence: 99%